ANALISIS SEMANTIK ANTOLOGI PUISI SENANDUNG ASA KARYA SISWA SMAN 6 SURABAYA - Aisya Kurrotuain; Mukhzamilah (STKIP Subang, 2026)
This study aims to describe three types of semantic meaning, namely denotative, connotative, and grammatical meaning, contained in the Senandung Asa poetry anthology by students of SMAN 6 Surabaya. This study uses a qualitative approach with a descriptive method. The data source is the Senandung Asa poetry anthology, while the research data are in the form of words, phrases, lines, and stanzas containing denotative, connotative, and grammatical meanings. Data collection techniques are carried out through documentation and reading and taking notes. The results of the study show that 102 semantic data were found consisting of 26 data (25.5%) of denotative meaning, 36 data (35.3%) of connotative meaning, and 40 data (39.2%) of grammatical meaning. Grammatical meaning is the most dominant type of meaning and appears through the processes of affixation, reduplication, and composition. Connotative meaning is present through personification, metaphor, simile, hyperbole, and symbols, while denotative meaning is used to describe physical and factual reality straightforwardly. This finding shows that the poetry anthology Senandung Asa by students of SMAN 6 Surabaya displays the use of the three types of semantic meaning studied, with variations that reflect students' linguistic intuition and the influence of poetry learning at school.